Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine which statement must be true given that the average rate of change of [tex]\( g(x) \)[/tex] between [tex]\( x=4 \)[/tex] and [tex]\( x=7 \)[/tex] is [tex]\( \frac{5}{6} \)[/tex], we can use the definition of the average rate of change.
The average rate of change of a function [tex]\( g(x) \)[/tex] between [tex]\( x = a \)[/tex] and [tex]\( x = b \)[/tex] is calculated by:
[tex]\[ \frac{g(b) - g(a)}{b - a} \][/tex]
In this problem:
- [tex]\( a = 4 \)[/tex]
- [tex]\( b = 7 \)[/tex]
- The average rate of change is [tex]\( \frac{5}{6} \)[/tex]
Substitute the given values into the formula:
[tex]\[ \frac{g(7) - g(4)}{7 - 4} = \frac{5}{6} \][/tex]
Simplify the denominator:
[tex]\[ \frac{g(7) - g(4)}{3} = \frac{5}{6} \][/tex]
To isolate [tex]\( g(7) - g(4) \)[/tex], multiply both sides of the equation by 3:
[tex]\[ g(7) - g(4) = 3 \times \frac{5}{6} \][/tex]
[tex]\[ g(7) - g(4) = \frac{15}{6} \][/tex]
[tex]\[ g(7) - g(4) = \frac{5}{2} \][/tex]
Therefore, the statement that must be true is:
[tex]\[ \frac{g(7) - g(4)}{7 - 4} = \frac{5}{6} \][/tex]
This corresponds to the third choice:
[tex]\[ \boxed{\frac{g(7) - g(4)}{7 - 4} = \frac{5}{6}} \][/tex]
Hence, the correct statement from the options provided is the third one.
The average rate of change of a function [tex]\( g(x) \)[/tex] between [tex]\( x = a \)[/tex] and [tex]\( x = b \)[/tex] is calculated by:
[tex]\[ \frac{g(b) - g(a)}{b - a} \][/tex]
In this problem:
- [tex]\( a = 4 \)[/tex]
- [tex]\( b = 7 \)[/tex]
- The average rate of change is [tex]\( \frac{5}{6} \)[/tex]
Substitute the given values into the formula:
[tex]\[ \frac{g(7) - g(4)}{7 - 4} = \frac{5}{6} \][/tex]
Simplify the denominator:
[tex]\[ \frac{g(7) - g(4)}{3} = \frac{5}{6} \][/tex]
To isolate [tex]\( g(7) - g(4) \)[/tex], multiply both sides of the equation by 3:
[tex]\[ g(7) - g(4) = 3 \times \frac{5}{6} \][/tex]
[tex]\[ g(7) - g(4) = \frac{15}{6} \][/tex]
[tex]\[ g(7) - g(4) = \frac{5}{2} \][/tex]
Therefore, the statement that must be true is:
[tex]\[ \frac{g(7) - g(4)}{7 - 4} = \frac{5}{6} \][/tex]
This corresponds to the third choice:
[tex]\[ \boxed{\frac{g(7) - g(4)}{7 - 4} = \frac{5}{6}} \][/tex]
Hence, the correct statement from the options provided is the third one.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.